The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pca.1287
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methods for heavy metals in herbal medicines

Abstract: In this review, we discuss in detail several commonly used and sensitive analytical techniques, including atomic absorption spectrometry, inductively coupled plasma optical emission spectrometry or mass spectrometry, X-ray fluorescence spectrometry, high-performance liquid chromatography, differential pulse polarography, neutron activation analysis and anodic stripping voltammetry. We also provide some application examples of these analytical techniques for heavy metals in herbal medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 68 publications
1
42
0
3
Order By: Relevance
“…Primarily, certain heavy metals are a regular component of traditional Indian and Chinese herbal remedies and are sometimes still intentionally added to traditional herbal preparations, even though their toxicity has rendered their use no longer acceptable [24,[74][75][76]. For example, heavy metals are neurotoxic and have repeatedly been correlated with the incidence of seizures [43].…”
Section: Environmental Contaminantsmentioning
confidence: 98%
“…Primarily, certain heavy metals are a regular component of traditional Indian and Chinese herbal remedies and are sometimes still intentionally added to traditional herbal preparations, even though their toxicity has rendered their use no longer acceptable [24,[74][75][76]. For example, heavy metals are neurotoxic and have repeatedly been correlated with the incidence of seizures [43].…”
Section: Environmental Contaminantsmentioning
confidence: 98%
“…It has been observed that the increasing demand for medicinal plants and herbal medicines, by itself, has led to a reduction in the quality of the product offered. The lack of information among producers about the care needed in each stage of production, from the harvest or the obtaining of the raw material to the final processing, and the shortage of trained professionals in the industry, also contribute to the low quality of the products or products that have poor quality (Carvalho et al, 2010;Zaroni et al, 2004 (Gautam et al, 2010;Yuan, Chapman, Wu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Neutron activation analysis technique, which mainly deals with solid samples, can avoid these problems (Orvini and Speziali, 1998). Instrumental neutron activation analysis (INAA) has excellent sensitivity and rapidity and the advantage of being largely insensitive to matrix effects; it also has precision and can execute simultaneous multi-element determinations (Yuan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the nature and sources of herbal medicines, they are sometimes contaminated with toxic heavy metals such as lead, arsenic, mercury and cadmium, which impose serious health risks to consumers (Yuan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%